The Concept of Monotheism in the Last Letter in the Text of the Qur'an - Besari, Anam (Jurnal Paradigma, 2021)
In religion there is no such thing as belief, meaning that every believer with their ownl level of belief will practice that religion. The stronger their level of belief, the more diligent they are and the more obedient they are to their religion.Departing from there, Islam also teaches how to know the God who created it or as the Creator/ the Kholiq. This realm is often referred to as the lesson of monotheism.Tauhid is one of the ways in Islam to know more about his God in this case is the God of Allah SWT the one. Because a person knows his God better and closer to his God, a person who is closer to his God will be more diligent and more obidient to his religion. Someone who is obidient to his religion they will find peace and comfort in carrying put the teachings of his religion. And when a person has felt peace and comfort in carrying out the teachings of his religion they will always find a happines in this life and the here after. Tauhid in Islam there are several levels of this can be seen visually what is written in Surah An Naas, where it is mentioned and arranged in a letter order, namely the first surah is about Tauhid Rububiyah, the second surah is Tauhid Mulkiyah, and the Third surah is Tauhid Uluhiyah.